The effect of audit committee charateristics on audit fees and audit opinion with moderating effect of audit committee gender - Lai, James Adrian T. (Animo Repository, 2022)
The audit quality of various entities can be affected by numerous factors, one of which may be audit committee characteristics. This paper examines the effect of audit committee characteristics on audit fees and audit opinion with audit committee gender as a moderating variable. Using a sample of non-banking and non-financial PSE-listed firms from the period of 2014-2018, this study looks into how these audit committees’ characteristics affect the audit quality proxied by audit fees and audit opinions. A panel regression model analysis and moderated regression analysis will be conducted on these samples of firms. The researchers hypothesize that independent variables, specifically the audit committee's financial expertise, size, independence, experience, and meeting frequency, have a significant effect on audit fees and audit opinion along with the implication of gender present in the audit committee. Additionally, non-audit fees, return on assets, current ratio, financial leverage, cash flow from operations, incurrences of loss, market to book value ratio, and percentage change in sales.